Relationship between Serum Dehydroepiandrosterone Levels and Heart Ejection Fraction in Heart Failure Patients - Rima Hayyu Chrisnanda; M. Robiul Fuadi; S.P. Edijanto; M. Yusuf (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Cardiovascular disease is still a serious problem in the world of health. Life expectancy after being diagnosed with heartfailure is 50% and 10% for 5 and 10 years. Steroid hormones such as Dehydroepiandrosterone (DHEAS) havecardioprotective effects by inhibiting the formation of atherosclerotic plaque, pulmonary artery vasodilators, and protectingcardiomyocytes. DHEAS levels decrease with age. Decreased DHEAS levels are associated with an increased risk ofcardiovascular disease. This study aimed to know the relationship between DHEAS levels in serum and ejection fractions inheart failure patients. This cross-sectional study used a sample of 34 people aged > 30 years who had been diagnosed withheart failure by a specialist in the Department of Cardiology and Vascular Medicine. The diagnosis of heart failure usesEchocardiography to determine the ejection heart fraction. DHEAS levels were taken from venous blood and examinedusing the CLEIA method with an IMMULITE device (Siemens Healthineers, Germany). Statistical analysis was performed bySpearman correlation test, with a significance level of p < 0.05. Thirty-four research subjects found that 13 patients had anejection fraction of 40% (Heart Failure with Reduced Ejection Fraction/HFrEF), 12 patients had an ejection fraction of 41-49%(borderline) and 9 patients had an ejection fraction of ≥ 50% (Heart Failure with Preserved Ejection Fraction/HFpEF).Spearman correlation test results obtained a correlation coefficient or r=0.357 with a value of p=0.038, which meant therewas a significant relationship between DHEAS with ejection fraction (p < 0.05). The lower the DHEAS level, the ejectionfraction would also be lower. Further with age, DHEAS levels get lower. The lower the DHEAS level, the lower the ejectionfraction.